A call to action—next steps for vision 20/20. Issue 2 (6th May 2015) - McCavit, Jack; Berger, Scott; Grounds, Cheryl; Nara, Louisa
<x xml:space="preserve">Abstract</x> Process safety protects and enhances our individual health, our company's success, and our region's business economy. Companies that handle toxic, flammable, and explosive materials understand the importance of process safety and risk management. So do regulators. So should the community and other stakeholders. Individually, these stakeholders have been working for years to improve process safety performance. Accidents continue to occur. It is time to leverage our resources, knowledge, and skills to all strive for a common goal of great process safety performance. CCPS's Vision 20/20 describes that vision, which calls for effort from individual companies and effort that goes well beyond any individual company, indeed beyond the industries. © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 111–118, 2015